The development of Interactive Multimedia for Elementary School Students - Vivi Mairina; Hadiyanto Hadiyanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study aims to develop interactive multimedia effectively used in Theme 4 and theme 5 in the semester I in Grade V of elementary school with valid, practical and effective criteria. The type of research is research and development using the 4-D Thiagarajan model through four stages, namely design, define, develop, and disseminate. The instrument used is the instrument of validity, practicality, and effectiveness. Data analysis using a Likert scale by looking at the analysis of validation, practicality, and effectiveness. The limited trial was carried out on the fifth-grade students of SDN 08 Sungai Rumbai with 21 students. The results show that interactive multimedia-based learning media in the first semester of fifth-grade elementary school have met the valid, practical, and effective categories to improve students’ learning outcomes.